Claims of intangible interest as matrimonial property at Shari’ah Courts: a special reference to Kelantan,Terengganu and Malacca - Ibrahim, Norliah; Abd Ghadas, Zuhairah Ariff (UPM Press, 2017)
Most of the cases related to claims of matrimonial property or harta sepencarian are confined to existing personal property which existed or acquired during the marriage prior to the divorce, such as buildings, land, vehicles. However, many modern families are venturing into business either as a principal means of generating income or as an additional measure to generate income. This has resulted in interest in intangible interests such as shares and investments in business (in addition to tangible ones). With the changes in proprietary interest, it is perceived that the scope of claims on matrimonial property shall also be revolutionised to include claims of future earning and intangible interests. This paper analyses cases related to matrimonial property claims in Shari’ah courts in Kelantan, Terengganu and Malacca. The objective is to highlight scope of claims and approaches of the Shari’ah courts in dealing with matrimonial property claims related to intangible interest, such as business interest and future earnings. The research was based on doctrinal and statutory analysis.